PERAN TEORI KLASIK DALAM PEMBENTUKAN PEMIKIRAN EKONOMI MODERN - Juan Sibarani; Arnol Siagian; Bonaraja Purba (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2026)
Social conflict is an interesting social phenomenon to study and research. This has given rise to various conflict theories. Researching and studying social conflict is an interesting social phenomenon. As a result, many theories of conflict have been developed. To help us identify and understand the many conflict theories out there, a mapping of these theories is required. Broadly speaking, the theories can be divided into two categories: classical and modern. The following are the luminaries of classical sociological conflict theory: Nicolo Machiavelli, Thomas Hobbes, Jean Bodin, Polybus, and Ibn Khaldun. Conflict hypotheses were put forward by contemporary sociologists Lewis A. Coser, Ralf Dahrendorf, and Karl Marx. According to traditional conflict theory, conflict arises from the innate tendency of humans to dominate and interfere with each other, especially in terms of power. More sophisticated than structural functionalism, modern conflict theory was born out of criticism of the theory.